The Influence of Product Quality, Price and Social Media Marketing on Purchasing Decisions at Shopee E-Commerce (Survey of Students at the Faculty of Economics, Bhayangkara University, Jakarta) - K. Farhan Rizki Abdulaziz; Yayan Hendayana; Ari Sulistyowati (Draf Solusi Indonesia, 2024)
This research aims to investigate the influence of product quality, price, and marketing via social media on purchasing decisions on the Shopee e-commerce platform. This research focuses on students from the Faculty of Economics and Business, Bhayangkara University, Jakarta as respondents, with the aim of understanding their purchasing behavior in the context of e-commerce.This research uses a survey method by adopting a questionnaire as a tool to collect information. The respondents sampled in this research were students registered at the Faculty of Economics and Business, Bhayangkara University, Jakarta who actively made purchases via the Shopee platform. It is hoped that this research will provide an in-depth understanding of the elements that influence purchasing decisions on the Shopee e-commerce platform, especially among students within the Faculty of Economics and Business, Bhayangkara University, Jakarta. The practical implications of this research can help e-commerce platforms and businesses optimize their marketing strategies, improve product quality, and manage prices more effectively to attract consumers and influence purchasing decisions. In addition, this research also contributes to academic understanding of the dynamics of e-commerce and the factors that influence consumer behavior in a digital context.